-4(-10-6n)=2(9n-7)

Simple and best practice solution for -4(-10-6n)=2(9n-7) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -4(-10-6n)=2(9n-7) equation:



-4(-10-6n)=2(9n-7)
We move all terms to the left:
-4(-10-6n)-(2(9n-7))=0
We add all the numbers together, and all the variables
-4(-6n-10)-(2(9n-7))=0
We multiply parentheses
24n-(2(9n-7))+40=0
We calculate terms in parentheses: -(2(9n-7)), so:
2(9n-7)
We multiply parentheses
18n-14
Back to the equation:
-(18n-14)
We get rid of parentheses
24n-18n+14+40=0
We add all the numbers together, and all the variables
6n+54=0
We move all terms containing n to the left, all other terms to the right
6n=-54
n=-54/6
n=-9

See similar equations:

| 5d=3(d+6) | | 6n+3=16 | | 4(q-13)-12=-4 | | x2−9x−15=−5 | | (x*3)+5=20 | | x+2÷8=2 | | 167=60-x | | 2x-7=6(x+3) | | x-6-3x=-8-8x+5 | | 9y=10y-19 | | 11+5k=2+3k-3 | | 20-8u-8u=4(-5u-11) | | 12x^2=19x*10 | | 5•(x-7)-4=11 | | 4/9(x)=-8 | | 24+m+85=685 | | -18=10a+2 | | -16+11q=-14q+9(-19q+20) | | 4/9(x)=8 | | 7x=0.5(2x+4) | | 8x-45-10=15+6x | | 4b+12=84 | | B+9b+2=12 | | —16+z=20 | | /1x+11=15 | | 41/2x+7=12 | | 8/17=u/5 | | 7s-3s-4=20 | | 4.x=1/2 | | 1=12b | | -11-19b-16=-6+6(-5b-20) | | /x/1+11=15 |

Equations solver categories